Intracystic Primary Squamous Cell Carcinoma of the Breast: A Challenging Diagnosis - Vera Ramos; João Fraga; Teresa Simões; Margarida Figueiredo Dias (Case Reports in Obstetrics and Gynecology)
We report a case of a 36-year-old woman that presented with a painful mass in the outer quadrants of the left breast that had grown rapidly. Physical examination revealed a well circumscribed elastic mass and breast ultrasound showed a cyst measuring 26 mm with vegetation growing on the inner wall. Microscopic evaluation, after fine needle aspiration cytology (FNAC), suggested benign lesion. Tumorectomy was performed and the final diagnosis was a pure squamous cell carcinoma (SCC) of the breast. A simple mastectomy with sentinel node biopsy was performed. The histological study of the specimen revealed residual SCC and the sentinel lymph node was negative. The patient received 6 cycles of adjuvant chemotherapy and adjuvant radiotherapy. Four years later, the patient is free of disease.